Early versus Delayed Phacoemulsification and Intraocular Lens Implantation for Acute Primary Angle-Closure. (1st April 2020) - Lin, Yun-Hsuan; Wu, Cheng-Hsiu; Huang, Shih-Ming; Hsieh, Chen; Chen, Henry Shen-Lih; Ku, Wan-Chen; Sun, Ming-Hui; Su, Wei-Wen
Abstract : Purpose . To compare the effects of early phacoemulsification and intraocular lens implantation (phaco/IOL), delayed phaco/IOL after initial laser peripheral iridotomy (LPI), and conventional LPI alone in patients with acute primary angle-closure (PAC). Methods . Patients with acute PAC were included in the study, and those with secondary glaucoma, prior ocular trauma, or other ocular diseases and those who had undergone ocular surgeries previously were excluded. Patients were categorized into three groups: Group A, which underwent primary phaco/IOL after acute PAC; Group B, which underwent LPI initially after acute PAC, followed by phaco/IOL within 6 months; and Group C, which underwent LPI alone. The IOP control success at 12 months as well as changes in ocular characteristics and the number of antiglaucoma medications used after the treatment among the groups were evaluated. Results . Eighty-one eyes were included in the study: 24 eyes in Group A, 23 eyes in Group B, and 34 eyes in Group C. The linear mixed model analysis demonstrated considerable IOP control in Groups A and B. Visual acuity, anterior chamber depth (ACD), and angle width improved significantly in Groups A and B, but not in Group C. The number of antiglaucoma medications used was significantly higher in Group C than in Groups A and B. Conclusions . Patients who underwent phaco/IOL had better IOP control, improved vision, deeper ACD, and wider angle and required less antiglaucoma medications than those who underwent LPI alone. Performing phaco/IOL weeks to months after the initial LPI did not appear to adversely affect outcomes compared with those of early phaco/IOL.